Accuracy of capillary blood glucose for 50-g glucose challenge test for gestational diabetes screening - Boriboonhirunsarn D. (2023)
Purpose: To assess the accuracy of capillary blood glucose (CBG) compared to conventional venous plasma glucose (VPG) testing for 50-g glucose challenge test (GCT) in gestational diabetes (GDM) screening. Methods: A total of 300 women were enrolled and 50-g GCT for GDM screening was offered. At 1 h after glucose loading, CBG was evaluated by CONTOUR® PLUS glucose meter by well-trained nurses immediately after venipuncture for VPG. Results of CBG were compared with those from VPG to evaluate its accuracy. Women with venous plasma glucose > 140 mg/dL were offered 100-g OGTT for GDM diagnosis. Results: The mean age was 30.2 years and the mean gestational age at testing was 21.8 weeks. GDM was diagnosed in 34 women (11.3%). The mean VPG was 142.1 ± 32.9 mg/dL and the mean CBG was 129.3 ± 33.5 mg/dL. Mean difference was −12.3 ± 12.5 mg/dL, corresponding to −8.8 ± 11.4%. CBG significantly correlated with VPG with correlation coefficient of 0.929, p < 0.001. In the detection of abnormal 50-g GCT results (VPG ≥ 140 mg/dL), at 126 mg/dL cutoff, CBG had sensitivity of 92.5%, specificity of 81.8%, and positive and negative predictive values of 82.8%and 92%. None of the GDM would have been missed if CBG was used. Conclusion: CBG by a certified glucose meter could be considered as an alternative to conventional VPG testing for 50-g GCT for GDM screening using 126 mg/dL cutoff value.